Prospective evaluation of an assessment tool for technical performance of duodenoscopes. Issue 5 (17th November 2020) - Bang, Ji Young; Rösch, Thomas; Kim, Hyungjin Myra; Thakkar, Shyam; Robalino Gonzaga, Ernesto; Tharian, Benjamin; Inamdar, Sumant; Lee, Linda S.; Yachimski, Patrick; Jamidar, Priya; Muniraj, Thiruvengadam; DiMaio, Christopher; et al.
Abstract : Objective: While single‐use and detachable‐tip duodenoscopes have been recently developed to overcome risks of infection transmission, there are no reliable tools to objectively assess their technical performance. We evaluated the reliability and validity of a newly developed tool to assess the technical performance of reusable duodenoscopes. Methods: An assessment tool was developed to measure duodenoscope performance based on three distinct criteria: maneuverability, mechanical/imaging characteristics and ability to perform requisite interventions. The assessment tool was tested prospectively on duodenoscopes used in endoscopic retrograde cholangiopancreatography (ERCP) procedures at nine academic medical centers over a 6‐month period. The main outcome was reliability of the duodenoscope assessment tool, which was estimated using Cronbach's coefficient alpha (α). The secondary outcome was validity of the assessment tool. Results: The assessment tool evaluated technical performance of reusable duodenoscopes in 1080 ERCP procedures. Indications were biliary in 92.8% and pancreatic in 7.2% procedures. The overall Cronbach's coefficient α for maneuverability was 0.81, assessment of mechanical/imaging characteristics was 0.92, and ability to perform requisite interventions was 0.87. On multiple linear regression analysis, prolonged procedure duration, older patient age and pancreatic interventions were significantly positively associated with higher (worse) scores. Conclusions: The newly developed assessment tool appears reliable and valid for evaluating the technical performance of duodenoscopes. Registration: ClinicalTrials.gov Identifier: NCT04004533.